PELATIHAN PENULISAN ARTIKEL ILMIAH BAGI PENGHULU SEBAGAI TENAGA FUNGSIONAL - Ahmad Lahmi; Sobhan Sobhan; Mahyudin Ritonga; Kholidah Kholidah; Ronaldi Ronaldi (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The ability to write scientific articles and their publications requires continuous training, as part of the functional workforce requires these skills to support future career development. Therefore, this activity aims to provide training to the ruler in West Pasaman Regency in terms of writing and publication of scientific works. The activity is carried out with training, technically the service team provides theoretical explanations and demonstrates the steps of submitating articles to the targeted journal. The result of this activity is that trainees know the types of scientific work, platforms that can help write scientific articles, steps to submit articles in targeted journals.